Deciphering Spatial Variability and Kriging Mapping for Soil pH and Groundwater Levels - M Edi Armanto; Mohd Zuhdi; Dedi Setiabudidaya; Ngudiantoro Ngudiantoro; Elisa Wildayana; Agus Hermawan; Momon Sodik Imanudin (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Spatial variability of peatlands is mostly related to natural variations and environment. Thus, it is natural and manageable. This study aimed to determine deciphering spatial variability and kriging mapping for soil pH and groundwater levels. The study was conducted on peatlands in Seponjen Village, Kumpeh Sub-District, Muaro Jambi District, Jambi. The collected data were analyzed using ArcGIS 10.3 and Geostatistics. The validation analysis of soil pH showed good performance where the actual soil pH and the estimated results of soil pH had the same fluctuation pattern, with high reliability (r = 0.94) and accuracy (R2 = 0.89) positive. It means that the interpolation performance of soil pH data can be used to create soil pH maps. The soil pH on very thick peat (the area A) showed a strong autocorrelation with a variogram range of 768 m, while on medium peat (the area B) it showed an anisotropic tendency towards rivers with a maximum variability of 273 m. The depth of the groundwater levels in the two areas is autocorrelative, it has a spatial dependence where the variability of the groundwater levels is small at close ranges and increases at long distances.